Mercati di architettura in ferro costruiti nel sud del Portogallo. Origine, protagonisti e situazione attuale - Palomares Alarcón, Sheila (2022)
Although iron as a building material began to be used in Portugal in the 1840s in structures such as bridges, it was not until the 1870s that the first markets began to be built with this material. Probably inspired by Les Halles de Paris, markets began to proliferate throughout the country using iron as a construction material, normally combined with other materials for external facades. Over the years, some markets have been preserved, several have disappeared, and others have been restored with changes of use. After carrying out an in-depth bibliographic survey, an exhaustive archival work and extensive fieldwork, this article aims to analyse and present several case studies of little-known architectures and reflect on their future.